Fluorinated porphyrin-based theranostics for dual imaging and chemo-photodynamic therapy. Issue 20 (4th May 2020) - Zhang, Huaibin; Bo, Shaowei; Zeng, Kai; Wang, Jie; Li, Yu; Yang, Zhigang; Zhou, Xin; Chen, Shizhen; Jiang, Zhong-Xing
Abstract : A modular strategy facilitates the convenient and standardized preparation of multifunctional theranostics for cancer therapy. Abstract : Convenient strategies to transform regular liposomes or nano-micelles into multifunctional theranostics would be highly valuable in cancer therapy. Herein, we developed an amphiphilic fluorinated porphyrin dendrimer as a multifunctional "add-on" module which would self-assemble onto liposomal drug delivery systems and conveniently transform the liposomes into novel theranostics. Through cancer cells and murine xenograft tumor model assays, the theranostics showed valuable fluorescence/ 19 F magnetic resonance dual modal imaging and highly efficient chemo-photodynamic therapy. The modular strategy facilitates the convenient and standardized preparation of multifunctional theranostics.